The Cytotoxicity of Doxorubicin Can Be Accelerated by a Combination of Hyperthermia and 5-Aminolevulinic Acid - Hiromi Kurokawa; Hirofumi Matsui (MDPI AG, 2021)
Chemotherapy is cytotoxic to various cancer cells and as well as normal cells. Thus, treatments that demonstrate selective cytotoxicity for cancer cells are desired. The combination of chemotherapy and other cancer therapies can show synergic cytotoxicity, which may be a clue to the nature of the involved cancer cellar-specific damage. We previously reported a phenomenon whereby mitochondrial reactive oxygen species (mitROS) regulate the expression transporters involved in anticancer drug transport and mitROS production is increased by hyperthermia. Moreover, the uptake of 5-aminolevulinic acid (ALA) was enhanced by the increase in mitROS production. In this study, we investigated whether the combination of hyperthermia and ALA can enhance the cytotoxicity of doxorubicin. MitROS production and ALA-derived porphyrin accumulation by hyperthermia (HT) were increased in a murine breast cancer cell line. The expression of solute carrier 15A1 (SLC15A1) upregulated and an ATP-binding cassette subfamily G member 2 (ABCG2) downregulated by HT. Since SLC15A1 is an accumulating transporter for ALA, while ABCG2 is a porphyrin efflux transporter, porphyrin accumulation was enhanced. ABCG2 is also a doxorubicin efflux transporter. Thus, ALA treatment accelerates the intracellular concentration of porphyrin, which acts as a competitive inhibitor of doxorubicin. Indeed, the amount of intracellular doxorubicin was increased by a combination of HT and ALA. The cytotoxicity of doxorubicin was also enhanced. This enhancement was observed in the human breast cancer cell line while it was not seen in normal cells. The combination of HT and ALA treatment can enhance the cancer-specific cytotoxicity of doxorubicin.